Spectral functions from the functional renormalization group - Wambach, Jochen; Tripolt, Ralf-Arno; Strodthoff, Nils; von Smekal, Lorenz (Nuclear physics. A, Nuclear and hadronic physics, 2014)
In this article we wish to present a new method to obtain spectral functions at finite temperature and density from the Functional Renormalization Group (FRG). The FRG offers a powerful non-perturbative tool to deal with phase transitions in strong-interaction matter under extreme conditions and their fluctuation properties. Based on a thermodynamically consistent truncation we derive flow equations for pertinent two-point functions in Minkowski space-time. We demonstrate the feasibility of the method by calculating mesonic spectral functions in hot and dense hadronic matter using the quark-meson model as a simple example.
Gesehen am 31.08.2020